Pengaruh Tindakan Supervisi Terdapat Kinerja Auditor Internal Dengan Motivasi Dan Kerjasama Sebagai Variabel Intervenig (Studi Kasus Bank Negara Indonesia 1946 Palembang) - Poppy Indriani; Jaka Darmawan (Universitas Bandar Lampung (UBL), 2013)
Research on the supervision on job satisfaction measures have been carried out by previous researchers, but studies on the effect of supervisory actions and motivations of the performance is still rare. In this study that distinguishes it from previous research is here the researcher intends to reexamine the influence of variables on the performance of the act of supervision and motivation variables plus the variable cooperation as an intervening variable. This study uses an instrument questions for each variable.The primary data in this study was obtained from the Internal Auditor opinion on the perception of PT. BNI 46 who complete and return the questionnaire to the researcher. Data collected by the census, which is distributed to the 13 internal auditors in the Compliance Division operating in Palembang. Furthermore then analyzed statistically assisted program SPSS 17.0. The analysis technique used is the analysis of the path.